1965
DOI: 10.1063/1.1703223
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Diffraction Study of the Structures of C2H4 and C2D4

Abstract: lines are partially blended. Thus, it appears that Chiu's equations give very reasonable predictions for the intensities of this mixed magnetic-dipole-e1ectric-quadrupole transition.Wilkinson and Mulliken,2 using relatively poor uncalibrated photographic data on the a lIIgf-X ll;g+ system and employing line-strength formulas developed only for a ll;g+f-ll;g+ transition 9 (admittedly very tentatively), estimated Q/D=0.15, which is of the order of magnitude of the value obtained here. This presumably more precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
93
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(102 citation statements)
references
References 14 publications
9
93
0
Order By: Relevance
“…* Some important torsion angles are provided in Table 2. The Bartell, Roth, Hollowell, Kuchitsu & Young, 1965]. It is also observed that the bonds C (2) (3)i~,] bond lengths are also slightly shorter than the value of 1.764 (1)/~, found in tetrakis(methylthio)ethylene measured at 238K (Collins & Davis, 1978).…”
mentioning
confidence: 68%
“…* Some important torsion angles are provided in Table 2. The Bartell, Roth, Hollowell, Kuchitsu & Young, 1965]. It is also observed that the bonds C (2) (3)i~,] bond lengths are also slightly shorter than the value of 1.764 (1)/~, found in tetrakis(methylthio)ethylene measured at 238K (Collins & Davis, 1978).…”
mentioning
confidence: 68%
“…The structure of small organic liquid molecules can be investigated by different experimental techniques (for example electron 7 , neutron 8 and X-ray diffraction 9 , infrared 10 , Raman 11 and NMR 12 spectroscopy) or using theoretical approaches like ab initio calculations 13 , density functional theory 14 or integral equations 15 . Different simulation methods are available, as well, that apply interaction potential functions: molecular dynamics (MD) 16 and standard (Metropolis) Monte Carlo 17 simulations are the best known examples.…”
mentioning
confidence: 99%
“…The N-C2 bond distance of 1.325 (9)/~ is much shorter than the value of 1.452 (2)A reported by Ammon, Mazzocchi, Regan & Colicelli (1979), and indicates partial doublebond character; the planar conformation for this group also indicates that the state of hybridization of the N atom is sp 2. The C2=C3 bond length is 1.398 (10)/~ [normal double bond in ethylene 1.336 (2),~ (Bartell, et al, 1965)], and the twist angle around this bond is 1.6 (10) °. The low twist angle is due to the strong intermolecular H bonding between the NH and CO groups.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of substituted ethylenes have C=C bonds significantly longer than the bond in ethylene [1.336 (2)A; Bartell, Roth, Hollowell, Kuchitsu & Young, 1965;Kuchitsu 1966], e.g. trivinylborane, 1.370 (6)/~ (Foord, Beagley, Reade & Steer, 1975).…”
Section: Introductionmentioning
confidence: 99%